Implementasi Peraturan Daerah Kota Sorong Nomor 11 Tahun 2014 Tentang Kawasan Tanpa Rokok - Muhamad Faizal Arianto; Sariana Pangaribuan; Umra Safriani; Dinda Ramadhani; Eva Fitri Ramadhany; Wildo Loupatty; Merlin Regina Rumbarar; Irma Fitria Iskandar; Deasy C. Mara; Putri Karisma Wati1 (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Regional Regulation Number 11 of 2014 concerning Non-Smoking Areas was issued by the Sorong City Government in 2014 with the aim of creating an environment free from cigarette smoke. This regulation aims to change the behavior of people who smoke and emphasizes how important it is to create a supportive environment to stop smoking. The aim of this research is to find out whether the implementation of smoking-free areas has been implemented. This research uses a quantitative research design. The results of observations made in seven areas of non-smoking areas are that on average the implementation that has been carried out has not been implemented. In conclusion, the government must be more firm in implementing the policy of Sorong City Regional Regulation Number 11 of 2014 concerning No-Smoking Areas so that the policy can run evenly and provide socialization to the public regarding the policy of Sorong City Regional Regulation Number 11 of 2014 concerning No-Smoking Areas with the community's expectations. understand the policies made.